Research on Teaching Strategies of Jiangxi Folk Songs Choral Programme in Higher Education Music Education - Hu, Wenzhe (International Journal of Social Sciences and Public Administration, 2025)
Music education in colleges and universities is an important link in the cultivation of musical talents in China, and Jiangxi folk song chorus, as an important part of China’s traditional music culture, has a unique status and value in music education in colleges and universities. In this paper, starting from the analysis of the characteristics of Jiangxi folk song choral repertoire, the current situation of Jiangxi folk song choral repertoire in music education in colleges and universities has been investigated, and corresponding education and teaching strategies have been put forward to address the existing problems. The results of the study show that the implementation of teaching strategies such as optimising the curriculum, innovating teaching methods, and strengthening practical links can effectively enhance students’ interest in and identification with Jiangxi folk song chorus and improve the teaching effect. This study provides a useful reference for the teaching of Jiangxi folk song choral repertoire in music education in colleges and universities, and has certain significance for promoting the reform and development of music education in colleges and universities in China.